Treatment of chronic liver disease using cell‑engineered constructs: morphofunctional characteristics - M. Yu. Shagidulin; N. A. Onishchenko; A. V. Grechina; M. E. Krasheninnikov; A. O. Nikolskaya; E. A. Volkova; N. P. Mogeiko; N. A. Boiarinova; A. V. Lyundup; G. A. Piavchenko; L. I. Davydova; A. Yu. Arhipova; et al. (Вестник трансплантологии и искусственных органов)
Objective: to study the effectiveness of correcting the morphofunctional characteristics of the liver in an experimental model of chronic liver disease (CLD), using implanted cell-engineered constructs (CECs).Materials and methods. Experiments were carried out on male Wistar rats (n = 80) aged 6–8 months with an initial weight of 230–250 g. CLD was modeled by inoculating the rats with 60% CCl4 oil solution for 42 days based on a modified scheme. Microgel based on recombinant spidroin rS1/9 was used as a matrix for CECs fabrication. Allogeneic liver cells (LCs) and multipotent bone marrow-derived mesenchymal stem cells (BM-MSCs) from a healthy donor were used as the cellular component of the CECs. The effectiveness of the corrective effect of the implanted CECs was assessed in an experimental CLD model (n = 60) in two groups of rats: Group 1 (control, n = 20, 1 mL of saline solution was injected into the damaged liver parenchyma) and Group 2 (experimental, n = 40, CECs containing allogenic LCs and BM-MSCs in a 5 : 1 ratio in a volume of 1 mL were implanted into the damaged liver parenchyma). For long-term monitoring of the CEC state, the CECs were labeled by additional inclusion in Cytodex-3. The effectiveness of the regulatory effect of CECs on regenerative processes in the liver was evaluated using biochemical, morphological and morphometric techniques, as well as by flow cytometry at 90 days after implantation.Results. In the control group, the mortality rate in CLD was 25%. There was no death in the experimental group with CLD after CEC implantation. The CECs were found to have a corrective effect on the biochemical and morphological parameters of the liver in CLD during 90 days of follow-up, with concomitant preservation of structural cellular homeostasis in the implanted CECs. Conclusion. Implantation of CECs in the liver facilitates effective correction of CLD by activating regenerative processes in the damaged liver, which is due to long-term preservation of structural cellular homeostasis in the CECs.